Three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization crosslinking and preparation method thereof
By introducing Ti3C2Tx nanosheets and metal salt ice crystal polymer polymer polymer, a three-dimensional PPy-MXene composite aerogel was prepared, which solved the problem of structural decomposition during the charge and discharge process, and achieved high energy density and fast charge and discharge effects.
Patent Information
- Application Number
- CN202510086326.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing PPy conductive polymers have structural decomposition due to large volume expansion and contraction during charging and discharging, resulting in rapid attenuation of capacitors and limited cycle life.
By introducing Ti3C2Tx nanosheets and metal salt ice crystal polymerization and crosslinking technology, a three-dimensional PPy-MXene composite aerogel was prepared, and the polymerization reaction speed was controlled to achieve uniform crosslinking and form an excellent porous structure.
It realizes the structural stability and high energy density of PPy-MXene composite materials, has fast charging and discharging and good cycle stability, and is suitable for high-performance electrochemical devices.
Smart Images

Figure CN119798770A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage materials, and specifically relates to a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking and a preparation method thereof. Background Art
[0002] Energy problems are becoming increasingly serious, and people are in urgent need of high-performance energy storage devices. Three-dimensional structures have a large specific surface area, high structural stability, and a high density of active sites, which can accelerate the ion transfer rate and achieve a higher energy density. Conductive polymers have good conductivity, flexibility, and easy synthesis. Carbon-based nanomaterials have high specific surface area, low weight, controllable pore size distribution, and compatibility with other materials. Conductive polymers such as PPy undergo large volume expansion and contraction during the charge / discharge process, resulting in structural decomposition, rapid capacitance decay, and limited cycle life. Ti 3 C 2 T x The introduction of nanosheets alleviates the expansion problem of PPy during the charge and discharge process and promotes the 3 C 2 T x The structural stability of the MXene / PPy composite material. The introduction of PPy with pseudocapacitive properties can produce higher capacitance than pure MXene. The -F and other groups on the MXene surface make the MXene nanosheets show good hydrophilicity. It provides more nucleophilic reaction sites for the polymerization of pyrrole monomers and also provides Fe 2+ The ability to eliminate the electrostatic attraction between MXene NSs provides a prerequisite. However, if the polymerization reaction rate is not controlled, the internal structure of the polymer material will be uneven and the crosslinks will aggregate at a certain position. Therefore, it is necessary to control the reaction rate of pyrrole monomer and ferric chloride to control the generation of polypyrrole and ferrous chloride and then control the polymerization reaction rate. Summary of the invention
[0003] The purpose of the present invention is to provide a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking and a preparation method thereof, wherein ferric chloride is designed to be prepared into metal salt ice crystals, the melting of ice crystals is controlled at a certain temperature, and then the speed of the polymerization reaction is controlled to obtain a uniformly cross-linked three-dimensional PPy-MXene composite aerogel. PPy and MXene are composited to prepare a three-dimensional porous structure through metal salt ice crystal polymerization and cross-linking to achieve higher energy density.
[0004] To achieve the above object, the present invention provides a method for preparing a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking, comprising the following steps:
[0005] Step 1: Ti 3AlC 2 The initial product was synthesized by HCl and LiF etching method for 30-35 hours. The initial product was centrifuged to remove the lower precipitate for washing, and then ultrasonically treated. The upper clear liquid was centrifuged to obtain Ti with pH 5-6. 3 C 2 T x MXene solution;
[0006] Step 2: Take a certain amount of MXene, add water and ethanol to obtain a MXene solution of a preset concentration, then add pyrrole and ferric chloride ice crystals, react for 6 to 10 hours, and obtain a PPy-MXene composite hydrogel;
[0007] Step 3: Soak the PPy-MXene composite hydrogel in ultrapure water to remove excess salt, take out the composite hydrogel and pre-treat it by absorbing water on filter paper, fully refrigerate it in liquid nitrogen, and freeze-dry it to finally obtain a three-dimensional PPy-MXene composite aerogel polymerized and cross-linked by metal salt ice crystals.
[0008] Furthermore, the reaction temperature of step 1 is 30-40°C, and the freeze-drying temperature of step 3 is -50 to -60°C.
[0009] Furthermore, in step 2, the volume ratio of water to ethanol is 4:1.
[0010] Furthermore, in step 1, Ti 3 C 2 T x The concentration of the MXene solution is 12 mg / ml to 22 mg / ml; the concentration of the MXene solution prepared in step 2 is 12 mg / ml.
[0011] Furthermore, the ferric chloride ice crystals are obtained by freezing a ferric chloride solution.
[0012] Furthermore, the ferric chloride ice crystals are added at 0-5°C.
[0013] Furthermore, the mass ratio of the MXene to pyrrole is 1:(1.2-1.7); the MXene to FeCl 3 The mass ratio is 8:(2-4).
[0014] The present invention also provides a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking obtained by any of the preparation methods described above.
[0015] The present invention also provides an electrochemical device prepared from the three-dimensional PPy-MXene composite aerogel described above.
[0016] Furthermore, the electrochemical device is obtained by laser plastic forming technology, and the laser plastic forming uses an infrared laser and is carried out in an inert atmosphere. The power of the laser plastic forming is 30W.
[0017] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0018] The three-dimensional PPy-MXene composite gas condensate synthesized by a simple experimental method, which is cross-linked by polymerizing metal salt ice crystals, has an excellent pore structure and can achieve fast charging and discharging, and has high energy density and power density. Its excellent structure shapes its excellent mechanical properties. Its morphology has almost no change before and after using a 500g weight load, and it can be prepared in large sizes, indicating that it can be integrated and has good application prospects in actual production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the process flow for preparing PPy-MXene composite aerogel in Examples 1-3 of the present invention;
[0020] Figure 2 SEM images of PPy-MXene with different ratios of MXene and Py prepared in Example 2;
[0021] Figure 3 TEM and HRTEM (c) images of MXene (a) and PPy-MXene (b) prepared in Example 3, and a mapping image of PPy-MXene (d);
[0022] Figure 4 Schematic diagram of the contact angle of the self-supporting PPy-MXene composite material in the aerogel state prepared in Example 3;
[0023] Figure 5 is the XRD pattern of the three-dimensional self-supporting PPy-MXene composite aerogel prepared in Example 1-3;
[0024] Figure 6 is a schematic diagram comparing the reaction time of Example 2 containing pyrrole and not containing pyrrole;
[0025] Figure 7 is the XRD diagram of the reaction time of Example 2 containing pyrrole and not containing pyrrole;
[0026] Figure 8 This is a diagram showing the mechanical properties of the three-dimensional self-supporting PPy-MXene composite aerogel prepared in Example 3;
[0027] Fig. 9is the stress variation curve of the three-dimensional self-supporting PPy-MXene composite aerogel prepared in Example 3;
[0028] Fig.10 is a schematic diagram of a large-scale three-dimensional self-supporting PPy-MXene composite aerogel prepared in Example 3;
[0029] Fig.11 This is the electrochemical test performance diagram of the three-dimensional self-supporting PPy-MXene composite aerogel prepared in Example 3. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] The equipment used in the following examples include:
[0032] Scanning electron microscope (SEM): JEOL JSM-7001F;
[0033] Transmission electron microscope (TEM): JEM-2100PLUS;
[0034] X-ray diffractometer (XRD): Rigaku ULTIMALV;
[0035] Raman spectrometer: Horiba iHR-320 Raman spectrometer, excitation wavelength 532nm;
[0036] Electrochemical workstation: CHI 760E, Chenhua, Shanghai, China.
[0037] Example 1: Preparation of MXene
[0038] (1) Place 80 mL of HCl solution (9 mol / ml) in a polytetrafluoroethylene reactor, add 4 g of LiF and stir until it is completely dissolved. Slowly add 4 g of Ti over 0.5 h. 3 AlC 2 (MAX). Move the polytetrafluoroethylene reactor into an oil bath, stir at 35°C for 30-35h, and add 100ml of ultrapure water to terminate the reaction. Centrifuge the reaction solution at 3500rpm for 5min, pour out the supernatant, and leave the lower precipitate. Repeat the centrifugation and washing of the lower precipitate several times until the pH value of the solution is close to neutral (pH = 5-6); ultrasonicate at 70% power for 1h, and then centrifuge at 3500rpm for 1h, collect the upper clear liquid, and obtain a single-layer or few-layer MXene dispersion.
[0039] (2) Take out a certain amount of MXene dispersion and calibrate it by filtration or freeze-drying.
[0040] Example 2: Preparation of PPy-MXene composite hydrogel
[0041] (1) The MXene solution was prepared according to the concentration of MXene to obtain a concentration of 12 mg / ml. Water and ethanol (volume ratio 4:1) were used for concentration preparation. The purpose of using ethanol was to allow for better dispersion of pyrrole when it was added later.
[0042] (2) Take a certain amount of FeCl 3 6H 2 O prepared with 2.5M FeCl 3 solution, and prepared into FeCl by external conditions such as freezing 3 Ice crystal state.
[0043] (3) Pyrrole (Py) was added according to the mass ratio of MXene to pyrrole of 2:1, 2:3, and 2:4, respectively, and the mass ratio of MXene to FeCl 3 The mass ratio is 8:3. Add a certain amount of FeCl 3 The ice crystals fully reacted for 6 to 10 h to obtain the PPy-MXene composite hydrogel.
[0044] Example 3: Preparation of large-scale PPy-MXene composites
[0045] (1) After the reaction, the PPy-MXene composite hydrogel was taken out and immersed in ultrapure water, and the water was changed several times until the solution was clear and transparent.
[0046] (2) The PPy-MXene composite hydrogel was taken out and placed on filter paper to absorb the moisture and then freeze-dried for 12 hours to obtain the PPy-MXene aerogel.
[0047] (3) Preparation of large-sized PPy-MXene composites.
[0048] Example 4
[0049] The composite material was laser plasticized in an argon atmosphere, and electrochemical testing was performed after the interdigitated package was produced.
[0050] In step (3) of Example 2, the pore size is regulated by adjusting the ratio of PPy-MXene, such as Figure 2 As shown, 3:2 (the masses of Py and MXene, respectively) was selected in this experiment.
[0051] according to Figure 3It can be seen that MXene was successfully prepared and PPy-MXene composites were successfully synthesized.
[0052] according to Figure 4 The contact angle image shows that the PPy-MXene composite material described in step (3) of Example 3 has super hydrophilicity, indicating that the electrolyte can fully infiltrate it. Figure 4 This image of aerogel on a dandelion demonstrates its ultra-lightweight properties.
[0053] according to Figure 5 From the XRD patterns, it can be seen that the MXene initial material was successfully synthesized and the PPy-MXene composite material was successfully prepared.
[0054] according to Figure 6 Only FeCl was added 3 The changes in the reaction time when Py was not added and both substances were added. It can be seen that when pyrrole was not added, MXene was gradually oxidized to TiO as the reaction time increased. 2 (The bottom gradually turns white). However, no obvious changes were observed in the vial with Py added as the reaction time increased. Figure 7 As can be seen from the XRD pattern.
[0055] The mechanical properties of the composite materials in Examples 1-3 are studied as follows Figure 8-9 As shown, it can be seen that the morphology of the composite material does not change significantly before and after loading 500g weight ( Figure 8 ), and the material showed no obvious damage after being loaded with a stress of 2700 kPa at 80% deformation ( Fig. 9 ).
[0056] according to Fig.10 The successful large-scale preparation of this composite material shows the mass production and integrability of the material.
[0057] The electrochemical properties of the composite aerogel materials in Examples 1-3 are as follows: Fig.11 As shown in the figure, the composite aerogel generated after freeze drying is laser-shaped under infrared to create a finger structure, and then the finger structure is prepared into an electrode, and PVALiCl electrolyte is added to perform electrochemical testing on the Chenhua workstation. The composite aerogel material can be quickly charged and discharged and has good cycle stability (89.3%). It has excellent power density and energy density. At 8A g -1 The energy density is 70.3Wh Kg -1 , power density is 3892WKg -1 , has broad development prospects.
[0058] In summary, the present invention provides a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking and a preparation method thereof, using Py and FeCl 3 Ice crystals, and by controlling the melting of ice crystals, the speed of the oxidative polymerization reaction is ultimately controlled, slowly combining to form PPy and Fe 2+ , so that Fe 2+ It can be evenly dispersed inside the composite material, cross-linking the MXene sheets to generate an excellent porous network structure, and the generated PPy effectively reduces the tendency of MXene to be oxidized. Finally, an ultra-light three-dimensional PPy-MXene composite aerogel is obtained by freeze drying. The three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking has super hydrophilicity, allowing electrolyte ions to pass quickly and achieve rapid charging and discharging. Its excellent cycle stability and high energy and power density make it have broad application prospects.
[0059] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking, characterized in that: The following steps are involved: Step 1: Using Ti3AlC2 as raw material, the initial product is synthesized by HCl and LiF etching method after 30-35 hours. The initial product is centrifuged to remove the lower layer of precipitate for washing, and then ultrasonically treated, and the upper layer of the supernatant is centrifuged to obtain Ti3C2T with a pH of 5-6. x MXene solution; Step 2: Take a certain amount of MXene, add water and ethanol to obtain a MXene solution of a preset concentration, then add pyrrole and ferric chloride ice crystals, react for 6 to 10 hours, and obtain a PPy-MXene composite hydrogel; Step 3: Soak the PPy-MXene composite hydrogel in ultrapure water to remove excess salt, take out the composite hydrogel and pre-treat it by absorbing water on filter paper, fully refrigerate it in liquid nitrogen, and freeze-dry it to finally obtain a three-dimensional PPy-MXene composite aerogel polymerized and cross-linked by metal salt ice crystals.
2. The method for preparing a three-dimensional PPy-MXene composite aerogel based on polymerization and cross-linking of metal salt ice crystals according to claim 1, characterized in that: The reaction temperature of step 1 is 30-40°C, and the freeze-drying temperature of step 3 is -50 to -60°C.
3. The method for preparing a three-dimensional PPy-MXene composite aerogel based on polymerization and cross-linking of metal salt ice crystals according to claim 1, characterized in that: In step 2, the volume ratio of water to ethanol is 4:
1.
4. The method for preparing a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking according to claim 1, characterized in that: In step 1, Ti3C2T x The concentration of the MXene solution is 12 mg / ml to 22 mg / ml; the concentration of the MXene solution prepared in step 2 is 12 mg / ml.
5. The method for preparing a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking according to claim 1, characterized in that: The ferric chloride ice crystals are obtained by freezing a ferric chloride solution.
6. The method for preparing a three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking according to claim 1, characterized in that: The ferric chloride ice crystals are added at 0-5°C.
7. The method for preparing a three-dimensional PPy-MXene composite aerogel based on polymerization and cross-linking of metal salt ice crystals according to claim 1, characterized in that: The mass ratio of the MXene to pyrrole is 1:(1.2-1.7); the mass ratio of the MXene to FeCl3 is 8:(2-4).
8. A three-dimensional PPy-MXene composite aerogel based on metal salt ice crystal polymerization and cross-linking obtained by the preparation method according to any one of claims 1 to 7.
9. An electrochemical device, characterized in that: Prepared from the three-dimensional PPy-MXene composite aerogel described in claim 8.
10. The electrochemical device according to claim 9, characterized in that The electrochemical device is obtained by laser plastic forming technology, wherein the laser plastic forming uses an infrared laser and is carried out in an inert atmosphere. The power of the laser plastic forming is 30W.
Citation Information
Patent Citations
MXene / conductive polymer composite aerogel and preparation method thereof
CN108530889A
Preparation method of compressible MXene / polymer electromagnetic shielding aerogel
CN112831143A
Electroconductive hydrogel and devices with conducting polymers assembled around a 3D nanofiber framework
US20240263002A1
Mxene / metal composite aerogel, preparation method therefor and use thereof, and thermal interface material containing same
WO2021056851A1